2014
DOI: 10.1007/s00284-014-0627-3
|View full text |Cite
|
Sign up to set email alerts
|

Quorum Sensing Signalling and Biofilm Formation of Brewery-Derived Bacteria, and Inhibition of Signalling by Natural Compounds

Abstract: Bacteria use quorum sensing signalling in various functions, e.g. while forming biofilms, and inhibition of this signalling could be one way to control biofilm formation. The aim of this study was to evaluate the production of signalling molecules and its correlation with the biofilm formation capability of bacteria isolated from brewery filling process. A further aim was to study berry extracts and wood-derived terpenes for their possible quorum sensing inhibitory effects. Out of the twenty bacteria studied, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 40 publications
0
14
0
Order By: Relevance
“…Because previous studies indicated that AI-2-mediated QS is associated with biofilm formation in gut, oral, marine and brewery microbial communities (Kolenbrander et al 2010;Christiaen et al 2014;Liaqat et al 2014;Priha et al 2014), it is likely that many of the luxS genes collected in the present study, not only from R. albus but also from other bacteria, are probably involved in biofilm formation on feed particles for fiber degradation.…”
Section: Results and Discussion Detection Of Luxs Gene Sequencesmentioning
confidence: 95%
See 1 more Smart Citation
“…Because previous studies indicated that AI-2-mediated QS is associated with biofilm formation in gut, oral, marine and brewery microbial communities (Kolenbrander et al 2010;Christiaen et al 2014;Liaqat et al 2014;Priha et al 2014), it is likely that many of the luxS genes collected in the present study, not only from R. albus but also from other bacteria, are probably involved in biofilm formation on feed particles for fiber degradation.…”
Section: Results and Discussion Detection Of Luxs Gene Sequencesmentioning
confidence: 95%
“…Ecological studies of rumen microbial communities showed that biofilm formation commences with the adhesion of initial colonizers, mainly cellulose-and starch-degrading bacteria, to the feed particles, and their end-products are used as substrates of other colonizers for developing biofilm (Minato & Suto 1976, 1978Cheng et al 1984;McAllister et al 1994). Because previous studies indicated that AI-2mediated QS is associated with biofilm formation in gut, oral, marine and brewery microbial communities (Kolenbrander et al 2010;Christiaen et al 2014;Liaqat et al 2014;Priha et al 2014), it is likely that many of the luxS genes collected in the present study, not only from R. albus but also from other bacteria, are probably involved in biofilm formation on feed particles for fiber degradation.…”
Section: Results and Discussion Detection Of Luxs Gene Sequencesmentioning
confidence: 99%
“…Moreover, blueberry extract was outstanding in the inhibition of quorum sensing related swarming motility in P. aeruginosa and E. coli O157:H7 pathogens. Berry phenolic extracts, namely those from raspberry and cloudberry, were the most effective C. violaceum AHL signaling inhibitors in the study of Priha et al [113]. In addition, the cloudberry extract reduced the biofilm formation of the common brewery contaminant bacterium, Obesumbacterium proteus at the concentrations of 25 and 50 mg/L.…”
Section: Anti-quorum Sensing and Antibiofilm Effects Of Plant Phenolicsmentioning
confidence: 88%
“…Similarly, the phenolic extract of freeze‐dried cloudberry fruit led to a statistically significant reduction of biofilm formation of Obesumbacterium proteus (Priha et al . ).…”
Section: Discussionmentioning
confidence: 97%
“…Meanwhile, the compact threedimensional structures in a mature biofilm might hinder the diffusion of these compounds into the biofilm (Sandasi et al 2008). Similarly, the phenolic extract of freeze-dried cloudberry fruit led to a statistically significant reduction of biofilm formation of Obesumbacterium proteus (Priha et al 2014).…”
Section: Discussionmentioning
confidence: 99%